The dracula dilemma : tourism, identity and the state in Romania - Light, Duncan, 1965- (New directions in tourism analysis., 2012)
This book examines the way that Romania has negotiated Dracula tourism over the past four decades. During the communist period (up to 1989) the Romanian state did almost nothing to encourage such tourism but reluctantly tolerated it. However, some discrete local initiatives were developed to cater for Dracula enthusiasts that operated at the margins of legality in a communist state. In the post-communist period (after 1989) any attempt to censor Dracula has disappeared and the private sector in Romania has been swift to exploit the commercial possibilities of the Count.